2020
DOI: 10.3390/su12166559
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Rural Innovation and Sustainability Through Impact Assessment: A Review of Methods and Tools

Abstract: Assessing impacts in innovation contexts/settings with the aim of fostering sustainability requires tackling complex issues. Literature shows that key sources of this complexity relate to the need to integrate the local context; identify the underlying problems; engage key stakeholders; and reflect on their feedback throughout the innovation process. A systematic literature review on innovation impact assessment reveals that social impacts have been the most studied, thus, where promising methods and tools wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 66 publications
(124 reference statements)
0
6
0
Order By: Relevance
“…Having an efficient C&D strategy also allows a TN to achieve a high impact, which is defined as the societal, economic and environmental effect that EU projects have on society [15]. However, it often happens that the produced materials are not easily findable and accessible, hence actors that can benefit from TN results are not aware of their existence [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Having an efficient C&D strategy also allows a TN to achieve a high impact, which is defined as the societal, economic and environmental effect that EU projects have on society [15]. However, it often happens that the produced materials are not easily findable and accessible, hence actors that can benefit from TN results are not aware of their existence [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Co-innovation is still an abstract concept which combines systems theory, social learning, design and monitoring and evaluation and utilizes participatory multi-stakeholder methodologies (Botha et al, 2014;Dogliotti et al, 2014). As co-innovation has been widely conceptualized as a process, the integration of participatory environmental decision making into the process has become inevitable (Lee et al, 2020;UCT and UNITAR, 2006;Wu et al, 2014), where multi-stakeholders, including community are encouraged to take control over the development process and decisions over resources (Allen and Kilvington, 1999;Neumeier, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the rural context, the innovation process is challenged by the complex environment where it unfolds calling for diverse perspectives from stakeholders with various background (Douthwaite et al, 2017;Preskill and Gopal, 2014) and so their multiple perspectives have significant influence on decision-making (Graef et al, 2018;Hall et al, 2001;McNie, 2007). Bringing in their perspectives on the problem and their participative action is crucial to identify the underlying cause of the problem which can then motivate innovative thinking to find adaptive innovative solutions (Lee et al, 2020;Tecco et al, 2016). Lee et al (2020) have identified from literature review that stakeholders in their innovation projects are concerned with finding the fundamental cause of the problem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To spread TN results as far as possible and to ensure that the gained knowledge or exploitable foreground can benefit the whole society, a thorough communication and dissemination (C&D) plan must be structured at the beginning of the project [7,8]. This plan allows a TN to achieve a high impact, which is defined as the societal, economic, and environmental effect that EU projects have on society [9]. In other words, achieving high impact means that TNs successfully provide access to meaningful, practice-oriented knowledge to targeted actors.…”
Section: Introductionmentioning
confidence: 99%